2022
DOI: 10.1021/accountsmr.2c00004
|View full text |Cite
|
Sign up to set email alerts
|

Li–Garnet Solid-State Batteries with LLZO Scaffolds

Abstract: Parameters for energy density calculations, charging process schematics, calculated gravimetric and volumetric energy densities, calculated current densities vs pore sizes (PDF)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Since the discovery of Li 7 La 3 Zr 2 O 12 (LLZO) solid-state electrolytes (SSEs) and the realization of their high potential to replace combustible organic electrolytes in Li-ion batteries [1][2][3][4][5] and voids. [30][31][32][33][34][35] On the one hand, the formation of voids during stripping can be mitigated by the larger surface area of the LLZO/Li interface in the scaffold compared to dense LLZO ceramics. On the other hand, Li can be stored in the pores of the LLZO scaffold during Li deposition, thereby avoiding dynamic changes in cell volume.…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of Li 7 La 3 Zr 2 O 12 (LLZO) solid-state electrolytes (SSEs) and the realization of their high potential to replace combustible organic electrolytes in Li-ion batteries [1][2][3][4][5] and voids. [30][31][32][33][34][35] On the one hand, the formation of voids during stripping can be mitigated by the larger surface area of the LLZO/Li interface in the scaffold compared to dense LLZO ceramics. On the other hand, Li can be stored in the pores of the LLZO scaffold during Li deposition, thereby avoiding dynamic changes in cell volume.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of ZELMB‐s, the host structure is initially considered empty. [ 19 ] Accordingly, during Li deposition into the host, the cell volume and the VED remain constant until over‐plating occurs, where the deposited Li displaces an equivalent volume of solid electrolyte. Accordingly, during over‐plating, the cell volume increases and the VED decreases.…”
Section: Resultsmentioning
confidence: 99%
“…estimated the GED and VED of solid‐state batteries based on porous LLZO host structures for multi‐layer pouch cells. [ 19 ] They showed that trilayer‐structures reach VED of 975 Wh L −1 but GED below 275 Wh kg −1 , while bi‐layer structures achieve slightly higher GED of up to 285 Wh kg −1 . Bilayer structures with 20 µm dense plus 50 µm porous (70 %) layers have been shown to achieve 329 Wh kg −1 and 972 Wh L −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, the calculations were performed for a full cell consisting of a porous/dense LLZO membrane, and an NMC811 cathode with an areal capacity of 3 mAh cm −2 , as recently reported in our work (see ref. [44,45] for details). The anode side is designed to be anode-free.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%